Effectiveness of Warm Compress on Labour Pain Relief in Primiparturients During the First Stage of Labour: Quasi-Experimental Study - Patel, Shital; Prakasam, Anita; Patel, vruti; Shivani, Shivani; Sharon, Sharon (Journal of Neonatal Surgery, 2025)
Labour pain is one of the most intense forms of pain experienced by women, particularly during the first stage of labour, which includes the latent and active phases. Effective pain management is a crucial aspect of obstetric care. While pharmacological methods are commonly used, there is a growing preference for non-pharmacological interventions that offer relief without medical side effects. Warm compress therapy, involving the application of heat to specific areas such as the lumbar and sacral regions, has been recognized for its potential to reduce pain and enhance comfort during labour.Objective: The present study aimed to evaluate the effectiveness of warm compresses in reducing labour pain in the lumbar and sacral areas during the first stage of labour among periparturient admitted to a selected hospital in Vadodara.Methods: A quantitative approach with a quasi-experimental design was adopted. The study included 60 primiparturients selected through non-probability convenience sampling. The participants were divided into experimental and control groups, and pain levels were assessed using the Numerical Pain Intensity Scale before and after the intervention. The experimental group received warm compress therapy, while the control group received standard care. Results: Pre-test findings indicated no statistically significant difference in pain levels between the experimental (mean = 7.93±1.08) and control groups (mean = 7.86±0.97) (t=0.251, p=0.803). However, post-test results showed a significant reduction in pain in the experimental group (mean = 6.50±1.08) compared to the control group (mean = 8.06±0.73) with a mean difference of 1.57 (t=6.861, p=0.001), indicating a statistically significant effect of the warm compress intervention.Conclusion: The study concludes that warm compress therapy is an effective non-pharmacological method for reducing labour pain in the lumbar and sacral regions during the first stage of labour. Its integration into routine obstetric care may improve the childbirth experience for primiparturients